Enzyme-induced carbonate precipitation on concrete crack repair - Goh, Charlize Yun Fang (Nanyang Technological University, 2024)
This report explores the feasibility of Enzyme-Induced Calcium Carbonate Precipitation (EICP) as a sustainable method for concrete crack repair. Utilizing soybean-derived urease, the method promotes eco-friendly and cost-effective calcium carbonate deposition. Key experiments assessed the influence of settling time, solution retention, and application techniques on EICP's performance. Results indicated that overnight solution retention and effective containment notably enhanced crack sealing and water impermeability, while a 10-minute settling time improved calcium carbonate deposition consistency.